A method for enhancing the applied voltage performance of non-precious metal Fe-NC catalysts
By applying voltage to the Fe-N-C catalyst under normal temperature and pressure, the active site is activated, and the problems of low catalyst performance and difficult industrial preparation are solved, and efficient and environmentally friendly catalyst performance improvement and feasibility of large-scale production are achieved. .
Patent Information
- Application Number
- CN202211195212.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-09-28
AI Technical Summary
The kinetics of existing Fe-N-C catalysts in oxygen reduction reactions are slow, and large-scale industrial preparation is difficult to achieve. Traditional processes have problems with low catalyst yields and environmental pollution.
By using the applied voltage performance enhancement method, the Fe-N-C catalyst solid powder is connected to the metal conductive support at normal temperature and pressure, and applied voltage to process it, which enhances the activation of the active site of the catalyst and improves its semi-stereologic under acidic and alkaline conditions. Wave potential and power density.
It significantly improves the intrinsic activity and long-term stability of Fe-N-C catalysts, achieves high-power density fuel cell performance, and is simple in process and environmentally friendly, without producing three wastes, which is suitable for large-scale industrial preparation.
Smart Images

Figure HDA0003870061340000011 
Figure HDA0003870061340000012 
Figure HDA0003870061340000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy materials, and belongs to the industrial production and application of high-performance non-precious metal Fe-NC catalysts, and specifically relates to a method and process for enhancing the applied voltage performance of Fe-NC catalysts. Background Art
[0002] Environmentally friendly, pollution-free and high-energy-density hydrogen proton exchange membrane fuel cell (PEMFC) new energy vehicles have been widely anticipated. However, the oxygen reduction reaction (ORR), one of the most critical reactions of PEMFC, has very slow kinetics, which limits the commercial application of PEMFC. At present, platinum-based metal catalysts are usually used to partially solve this problem, but the high price of platinum metal and the defects of easy poisoning and deactivation limit its application in PEMFC. Therefore, the exploration and development of efficient, durable and inexpensive non-precious metal catalysts has attracted extensive research by researchers. Fe-NC catalysts are considered to be the only choice because of their high activity and stability. However, even the performance of the most advanced Fe-NC catalysts still cannot completely replace platinum-based catalysts, so many processes have been developed to further improve the performance of Fe-NC catalysts. For example, Chinese patent application CN113054205A discloses a heat treatment process for improving the activity of non-precious metal catalysts, wherein the heat treatment process refers to a certain low-temperature insulation treatment of the catalyst on the basis of retaining the traditional high-temperature calcination treatment, and the process partially improves the performance of the Fe-NC catalyst. Chinese patent application CN113013428A discloses a preparation method and application of a Fe, Co bimetallic doped mesoporous carbon oxygen reduction catalyst. The method further improves the performance of the Fe-NC catalyst by preparing a FeCo-NC catalyst, and the electrocatalytic performance is improved under acidic conditions.
[0003] However, most of the catalysts involved in the prior art have very low yields, which makes it difficult to prepare them industrially on a large scale. Unlike the above methods, the external voltage performance enhancement method proposed in this patent is conducive to the large-scale preparation of Fe-NC catalysts, and it can be operated at room temperature and pressure, which is environmentally friendly and does not produce three wastes. In addition, it has some obvious advantages, such as easy adjustment of oxygen / nitrogen functional groups, significant activation of the inherent active site types such as FeN4 active sites by adjustment, and avoidance of catalyst agglomeration caused by liquid phase treatment. This helps to greatly improve the intrinsic activity and long-term stability of Fe-NC catalysts, and has very important application prospects. Summary of the invention
[0004] The present invention provides a method and process for enhancing the performance of a non-precious metal Fe-NC catalyst by applying an external voltage. The invention innovatively proposes a new method for enhancing the performance of a catalyst solid powder by applying an external voltage, so that the half-wave potential of the treated Fe-NC catalyst increases by 5 to 20 mV under acidic and alkaline conditions, and shows a 0.75 W / cm -2 The high power density of Fe-NC catalysts can be achieved by applying external voltage performance enhancement, so the external voltage performance enhancement method is beneficial to the improvement of Fe-NC catalyst performance. Compared with the traditional untreated non-precious metal catalysts, the catalysts treated with external voltage performance enhancement have significantly increased catalytic activity in the ring-disk electrode test. More importantly, they also show higher power density in actual fuel cells, which shows that the solid phase activation method has high practical commercial value and has important reference value for the improvement of catalyst preparation process and scale-up production.
[0005] In order to achieve the purpose of the invention, a method and process for enhancing the applied voltage performance of a non-precious metal Fe-NC catalyst is invented. The technical solution adopted by the present invention includes the following specific steps:
[0006] Step 1: taking a certain amount of Fe-NC catalyst solid powder and placing it in a container with two ends open or a flat container. The Fe-NC catalyst solid powder is placed in the container with two ends open or the flat container in a continuous and coherent manner, such as filling the diameter surface of a tubular container or not filling it up and placing it axially continuously, placing it in a continuous linear manner in a flat container, or stacking it in a pile shape, etc.;
[0007] Wherein, the Fe-NC catalyst is commercially available or homemade, such as a Fe-NC catalyst obtained by high-temperature pyrolysis, low-temperature pyrolysis, solid-phase synthesis or liquid-phase synthesis; the certain amount is in the mg to g level, and can reach the kg level under the conditions allowed by the device;
[0008] Step 2: Connecting two ends of the Fe-NC catalyst solid powder placed continuously in step 1 to a metal conductive carrier such as a metal wire to form a processing device;
[0009] Wherein, the metal conductive carrier is made of silver, copper or aluminum alloy;
[0010] Step 3: Under normal temperature, normal pressure and a certain atmosphere, the metal conductive carrier is connected with a power supply device to form a closed loop circuit;
[0011] Wherein, the certain atmosphere is one of air, nitrogen or oxygen, and the power supply device is preferably a constant voltage DC power supply;
[0012] Step 4: Confirm that the conductive carrier is not short-circuited to avoid subsequent short-circuit situations;
[0013] Step 5: Turn on the power supply device, apply a certain voltage, and keep the constant voltage stable for a period of time;
[0014] Wherein, the certain voltage is 5V to 30V; the period of time is 0.5h to 10h;
[0015] Step 6: Take out the treated solid powder, without adding any activator and without generating any three wastes, and fully grind and crush to obtain the Fe-NC catalyst with enhanced performance.
[0016] In step 2 of the present invention, the distance between the metal conductive supports at both ends of the Fe-NC catalyst solid powder can be adjusted as needed, such as 0.5 cm-50 cm.
[0017] The performance-enhanced Fe-NC catalyst has an Fe content of 0.01 to 1.5 at%, and a N content of 1 to 15 at%. Compared with the unenhanced Fe-NC catalyst, the specific surface area is increased by more than 20%, the conductivity is increased by more than 30%, and in addition to the FeN x In addition to the active site, FeN x -ketone active site.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] Compared with Fe-NC catalysts prepared by traditional liquid phase impregnation or solid phase pyrolysis methods, the catalyst prepared by applied voltage has better oxygen reduction reaction catalyst performance. Compared with Fe-NC catalysts prepared by traditional processes, the half-wave potential of Fe-NC catalysts enhanced by applied voltage increased by 5 to 20 mV under acidic and alkaline conditions, reaching 0.8 V and 0.9 V respectively. In addition, in actual fuel cell tests, it also showed an excellent performance of 0.75 W cm -2 Power density.
[0020] The reason is that voltage activation will help the corresponding active sites such as FeN xThe activation of active sites will help to fully exert the performance of active sites; on the other hand, the external voltage performance enhancement method will not destroy the original structure and morphology of the material, and maintain the original three-dimensional structure. In addition, the external voltage performance enhancement method can further improve the conductivity and porosity of the material. In the long-term application of fuel cells, the catalyst is required to have good conductivity, and the increase in conductivity caused by the external voltage performance enhancement helps the performance release of the catalyst during operation, and the increase in porosity will also help to further release the catalyst performance by exposing more active sites. Therefore, the external voltage performance enhancement treatment helps the application of Fe-NC catalysts in fuel cells to a certain extent, which is particularly important for practical fuel cell applications.
[0021] In addition to improving the performance of the catalyst, the most important thing about this method is that it is simple, feasible and efficient, does not require any water or organic solvent, does not need to add any additives, is environmentally friendly and does not produce any three wastes, can prepare catalyst materials in large quantities, and is very suitable for industrial production. In short, the Fe-NC catalyst material prepared by the present invention with enhanced applied voltage performance has excellent catalytic performance, performs well in the practical application of proton exchange membrane fuel cells, and may have unparalleled advantages in industrial preparation and scaled-up production. This method of enhanced applied voltage performance can also be used as a reference in the preparation processes of other heteroatom-doped carbon and non-precious metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to make the technical solution of the present invention easier to understand, the embodiments applied by the present invention will be clearly described through the following drawings, and the following drawings only show some embodiments of the present invention and do not limit the scope of the present invention.
[0023] Figure 1 The characterization diagrams corresponding to Example 1 and Comparative Example 1;
[0024] Wherein (a) is a scanning electron microscope (SEM) image of Example 1 of the external voltage performance enhancement method.
[0025] (b) SEM image of Comparative Example 1 without the applied voltage performance enhancement method.
[0026] (c) is the X-ray diffraction (XRD) spectra of Example 1 and the untreated Comparative Example 1 obtained by the applied voltage performance enhancement method.
[0027] (d) is a four-probe conductivity test diagram of Example 1 of the applied voltage performance enhancement method.
[0028] (e) is a four-probe conductivity test diagram of Example 1 without the external voltage performance enhancement method.
[0029] (f) is the surface area adsorption-desorption curve (BET) spectrum of Example 1 and the untreated Comparative Example 1 obtained by the external voltage performance enhancement method.
[0030] (g) is the element content distribution diagram of Example 1 obtained by the applied voltage performance enhancement method.
[0031] (h) is the element content distribution diagram of Example 1 obtained without the applied voltage performance enhancement method.
[0032] (i) is the atomic structure diagram of the FeN4-ketone active site of Example 1 obtained by the external voltage performance enhancement method.
[0033] Figure 2 It is a comparison diagram of polarization curves of Example 1 and Comparative Example 1;
[0034] Wherein (a) is a comparison diagram of the rotating disk polarization curves in alkaline medium of Example 1 and the untreated Comparative Example 1 obtained by the external voltage performance enhancement method.
[0035] (b) is a comparison diagram of the rotating disk polarization curves in acid medium of Example 1 and the untreated Comparative Example 1 obtained by the applied voltage performance enhancement method.
[0036] (c) is a comparison diagram of the polarization curves of Example 1 obtained by the external voltage performance enhancement method before and after 15,000 continuous CV cycle scans.
[0037] Figure 3 This is a performance test diagram of Example 1 in a fuel cell;
[0038] Wherein (a) is the polarization curve and power density curve of Example 1 obtained by the external voltage performance enhancement method in the hydrogen-air proton exchange membrane fuel cell test.
[0039] (b) is the polarization curve and power density curve of Example 1 obtained by the applied voltage performance enhancement method in the hydrogen-oxygen proton exchange membrane fuel cell test.
[0040] Figure 4 Characterization diagram corresponding to Example 2 and Comparative Example 2
[0041] Among them, (a) is the SEM image of Example 2 obtained by the external voltage performance enhancement method.
[0042] (b) is a SEM image of Comparative Example 2 in which no external voltage performance enhancement method was performed.
[0043] (c) is the XRD spectra of Example 2 obtained by the applied voltage performance enhancement method and the untreated Comparative Example 2.
[0044] Figure 5Comparison of polarization curves of Example 2 and Comparative Example 2 in different media
[0045] Wherein (a) is a comparison diagram of the rotating disk polarization curves in alkaline medium of Example 2 obtained by the external voltage performance enhancement method and the untreated Comparative Example 2.
[0046] (b) is a comparison diagram of the rotating disk polarization curves in acid medium of Example 2 obtained by the external voltage performance enhancement method and the untreated Comparative Example 2.
[0047] Figure 6 Characterization diagram corresponding to Example 3 and Comparative Example 3
[0048] Wherein (a) is a scanning electron microscope (SEM) image of Example 3 obtained by the external voltage performance enhancement method.
[0049] (b) is a scanning electron microscope (SEM) image of Comparative Example 3 in which no external voltage performance enhancement method was performed.
[0050] (c) is the XRD spectra of Example 3 and Comparative Example 3.
[0051] Figure 7 Comparison of polarization curves of Example 3 and Comparative Example 3 in different media
[0052] Wherein (a) is a comparison diagram of the rotating disk polarization curves in alkaline medium of Example 3 obtained by the external voltage performance enhancement method and the untreated Comparative Example 3.
[0053] (b) is a comparison diagram of the rotating disk polarization curves in acid medium of Example 3 obtained by the external voltage performance enhancement method and the untreated Comparative Example 3. DETAILED DESCRIPTION
[0054] In order to make the technical solutions and effects of the present invention easier to understand, they are described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is limited to the following specific implementation modes. Any equivalent replacement or modification made to the technical solutions in the present invention, but does not depart from the scope of the technical solutions of the present invention and is similar to the spirit of the technical solutions of the present invention, should be within the protection scope of the present invention.
[0055] Example 1
[0056] The self-made polyaniline@2-methylimidazole zinc salt composite material (PANI@ZIF8) derived Fe-NC catalyst was treated by applying voltage performance enhancement method and process.
[0057] First, 2.15g of dimethylimidazole and 200mg of polyaniline were dissolved in 80mL of methanol, which was recorded as solution A. Then 10mg of FeCl3 and 1.95g of zinc nitrate hexahydrate were dissolved in 80mL of methanol, which was recorded as solution B. After solutions A and B were fully ultrasonicated and stirred evenly, solution A was mixed with solution B, and the resulting mixture solution began a liquid phase synthesis reaction, which was marked as solution C. Solution C was placed on a magnetic stirring table and stirred for 3h, and then allowed to stand for 12h. After standing, the solution was layered, and solution C was filtered and washed three times with methanol and ethanol respectively. The sample obtained by filtration was placed in a 60℃ oven and dried for 12h.
[0058] Then, the sample was placed in a tube furnace for the first pyrolysis, the pyrolysis temperature was 1000℃, and the holding time was 2h. The sample after the first pyrolysis was placed in an isopropanol solution containing 0.5g / L ferric chloride, ultrasonicated for 2h, and stirred for 6h. After the solution was stratified, the solution was filtered, and the obtained sample was washed three times with isopropanol and ethanol respectively, and the obtained filtered sample was placed in a 60℃ oven for 12h. Then, the dried sample was placed in a tube furnace for the second pyrolysis, the pyrolysis temperature was 750℃, and the holding time was 2h.
[0059] Finally, at room temperature, pressure and air atmosphere, weigh 20 mg of the solid sample powder obtained by the second pyrolysis and place it in the center of a glass tube container with a continuous length of about 0.5 cm along the axial direction, and connect copper wires at both ends of the solid powder to form a conductive closed loop. Connect the positive and negative poles of the DC power supply to the metal wires respectively. After confirming that the conductive loop is not short-circuited, turn on the power supply and set the voltage to 15V, and keep this voltage constant for 1 hour. After the time is up, take out the sample, and without any post-treatment, grind it thoroughly to obtain the Fe-NC catalyst enhanced by the applied voltage, which is marked as "Fe-NC-1" catalyst. The obtained "Fe-NC-1" catalyst has 0.64at% of Fe element, 4.53at% of N element, 584.19m 2 g -1 The specific surface area is 0.24972S m -1 Compared with the "Fe-NC-1-untreated" catalyst that has not been enhanced by voltage, the specific surface area of the performance-enhanced Fe-NC catalyst has increased by more than 50% and the conductivity has increased by more than 30%. (The "Fe-NC-1-untreated" catalyst that has not been enhanced by voltage has 0.95at% Fe, 6.34at% N, and 388.69m 2 g -1 The specific surface area is 0.18784S m -1 In addition, the active sites of Fe-NC-1 are x In addition, there are also ketone functional group-modified FeNx -ketone active site.
[0060] Example 2
[0061] The homemade polyaniline (PANI) derived Fe-NC catalyst was treated by applying voltage performance enhancement method and process.
[0062] First, 200 mg of polyaniline was dissolved in 80 mL of methanol, which was recorded as solution A. Then 10 mg of FeCl3 was dissolved in 80 mL of methanol, which was recorded as solution B. After solutions A and B were fully ultrasonicated and stirred, solution A was mixed with solution B, and the resulting mixture solution began a liquid phase synthesis reaction, which was marked as solution C. Solution C was placed on a magnetic stirring table and stirred for 3 hours, and then allowed to stand for 12 hours. After standing, the solution was stratified, and solution C was filtered and washed three times with methanol and ethanol respectively. The sample obtained by filtration was placed in a 60°C oven and dried for 12 hours.
[0063] Then, the sample was placed in a tube furnace for the first pyrolysis, the pyrolysis temperature was 1000℃, and the holding time was 2h. The sample after the first pyrolysis was placed in an isopropanol solution containing 0.5g / L ferric chloride, ultrasonicated for 2h, and stirred for 6h. After the solution was stratified, the solution was filtered, and the obtained sample was washed three times with isopropanol and ethanol respectively, and the obtained filtered sample was placed in a 60℃ oven for 12h. Then, the dried sample was placed in a tube furnace for the second pyrolysis, the pyrolysis temperature was 750℃, and the holding time was 2h.
[0064] Finally, at room temperature, pressure and air atmosphere, weigh 20 mg of solid sample powder obtained by the second pyrolysis and place it in the center of a glass tube container, with a continuous length of about 0.3 cm along the axial direction, and connect copper wires at both ends of the solid powder to form a conductive closed loop. Connect the positive and negative poles of the DC power supply to the metal wires respectively. After confirming that the conductive loop is not short-circuited, turn on the power supply and set the voltage value to 10V, and keep this voltage constant for 1 hour. After the time is up, take out the sample, and without any post-treatment, fully grind and crush to obtain the Fe-NC catalyst enhanced by the applied voltage, which is marked as "Fe-NC-2" catalyst.
[0065] Example 3
[0066] The self-made Fe-NC catalyst derived from 2-methylimidazole zinc salt (ZIF-8) was treated by applying voltage performance enhancement method and process.
[0067] First, 2.15 g of dimethylimidazole was dissolved in 80 mL of methanol, which was recorded as solution A. Then 10 mg of FeCl3 and 1.95 g of zinc nitrate hexahydrate were dissolved in 80 mL of methanol, which was recorded as solution B. After solutions A and B were fully ultrasonicated and stirred evenly, solution A was mixed with solution B, and the resulting mixture solution began a liquid phase synthesis reaction, which was marked as solution C. Solution C was placed on a magnetic stirring table and stirred for 3 hours, and then allowed to stand for 12 hours. After standing, the solution was layered, and solution C was filtered and washed three times with methanol and ethanol respectively. The sample obtained by filtration was placed in a 60°C oven and dried for 12 hours.
[0068] Then, the sample was placed in a tube furnace for the first pyrolysis, the pyrolysis temperature was 1000℃, and the holding time was 2h. The sample after the first pyrolysis was placed in an isopropanol solution containing 0.5g / L ferric chloride, ultrasonicated for 2h, and stirred for 6h. After the solution was stratified, the solution was filtered, and the obtained sample was washed three times with isopropanol and ethanol respectively, and the obtained filtered sample was placed in a 60℃ oven for 12h. Then, the dried sample was placed in a tube furnace for the second pyrolysis, the pyrolysis temperature was 750℃, and the holding time was 2h.
[0069] Finally, at room temperature, pressure and air atmosphere, weigh 20 mg of solid sample powder obtained by the second pyrolysis and place it in the center of a glass tube container, with a continuous length of about 0.5 cm along the axial direction, and connect copper wires at both ends of the solid powder to form a conductive closed loop. Connect the positive and negative poles of the DC power supply to the metal wires respectively. After confirming that the conductive loop is not short-circuited, turn on the power supply and set the voltage value to 15V, and keep this voltage constant for 1 hour. After the time is up, take out the sample, and without any post-treatment, fully grind and crush to obtain the Fe-NC catalyst enhanced by the applied voltage, which is marked as "Fe-NC-3" catalyst.
[0070] Comparative Example 1
[0071] The sample in Example 1 that was not enhanced by the applied voltage, i.e., the product obtained by the second pyrolysis, was marked as "Fe-NC-1-untreated" catalyst.
[0072] Comparative Example 2
[0073] The sample in Example 2 that was not enhanced by the applied voltage, i.e., the product obtained by the second pyrolysis, was marked as "Fe-NC-2-untreated" catalyst.
[0074] Comparative Example 3
[0075] The sample in Example 3 that was not enhanced by the applied voltage, i.e., the product obtained by the second pyrolysis, was marked as "Fe-NC-3-untreated" catalyst.
[0076] Figure 1A is the SEM image of Example 1. Figure 1 b is the SEM image of comparative example 1. By comparing the two SEM images, the tubular structure of PANI and the dodecahedral structure of ZIF8 are clearly observed, and the tubular structure and dodecahedral structure after the applied voltage performance enhancement treatment do not change significantly. This shows that after the applied voltage performance enhancement treatment, the sample still maintains the original carbon material morphology.
[0077] Figure 1 Figure c is the XRD spectra of Example 1 and Comparative Example 1. In the XRD spectra, the graphite (002) and (100) crystal planes did not shift, indicating that after the external voltage performance enhancement treatment, the sample still maintained the original carbon material structure.
[0078] Figure 1 (d) is the four-probe conductivity diagram of Example 1. Figure 1 e is the four-probe conductivity diagram of comparative example 1. The specific surface area of example 1 is 0.24972 S m -1 The specific surface area of comparative example 1 is 0.18784 S m -1 , therefore, compared with Comparative Example 1, the conductivity of Example 1 increased by more than 30%.
[0079] Figure 1 f is the BET graph of Example 1 and Comparative Example 1. The data in the spectrum were calculated, and the specific surface area of Example 1 was 584.19 m 2 g -1 The specific surface area of comparative example 1 is 388.69 m 2 g -1 Therefore, compared with Comparative Example 1, the specific surface area of Example 1 increased by more than 50%.
[0080] Figure 1 g is the element content diagram of Example 1. The diagram shows that Fe-NC-1 has 82.84 at% of C element, 0.64 at% of Fe element, 4.53 at% of nitrogen element, and 11.99 at% of oxygen element.
[0081] Figure 1 h is the element content diagram of Comparative Example 1. The diagram shows that Fe-NC-1-untreated has 85.08 at% of C element, 0.95 at% of Fe element, 6.34 at% of nitrogen element, and 7.63 at% of oxygen element.
[0082] Figure 1 1 is a structural diagram of the FeN4-ketone active site of Example 1. The figure shows the formation of new FeN4-ketone active sites after the voltage performance is enhanced.
[0083] Figure 2Figure a is a comparison of the oxygen reduction polarization curves of the rotating ring disk electrode in alkaline medium of Example 1 and Comparative Example 1. The electrolyte solution is 0.1M KOH, and the scan rate is 10mV / s. From the linear sweep voltammetry (LSV) curve after iR compensation and N2 background current subtraction, it can be seen that the half-wave potential of Example 1 treated with external voltage performance enhancement is 0.890V, which is 20mV higher than that of the untreated Comparative Example 1. It shows that the external voltage performance enhancement treatment has a significant effect.
[0084] Figure 2 Figure b is a comparison of the oxygen reduction polarization curves of the rotating ring disk electrode in the acid medium of Example 1 and Comparative Example 1. The electrolyte solution is 0.1M HClO4, and the scan rate is 10mV / s. From the linear sweep voltammetry (LSV) curve after iR compensation and N2 background current subtraction, it can be seen that the half-wave potential of Example 1 treated with external voltage performance enhancement is 0.800V, which is 20mV higher than that of the untreated Comparative Example 3. It shows that the external voltage performance enhancement treatment has a significant effect.
[0085] Figure 2 Figure c is a durability diagram of the oxygen reduction polarization curve of Example 1 tested by a rotating ring disk electrode in an acid medium. The electrolyte solution is 0.1M HClO4, and the scan rate is 10mV / s. The cycle condition is 15,000 cycles of cyclic voltammetry (CV) test at a voltage of 0.6V to 1.1V. From the linear sweep voltammetry curve (LSV) after iR compensation and N2 background current subtraction, it can be seen that the initial half-wave potential of Example 1 treated with solid phase voltage activation is 0.800V. After 15,000 CV cycles, it only drops by 25mV, indicating that the sample with enhanced applied voltage performance exhibits excellent durability.
[0086] Figure 3 Figure a shows the polarization curve and power density diagram of the proton exchange membrane fuel cell test in Example 1. The fuel cell preparation and test process: (1) CCM method to prepare MEA: the cathode and anode loadings are 4 mg / cm 2 , 0.2mg Pt / cm 2 (40% Pt / C JM); DuPont NC700 proton exchange membrane, diffusion layer SGL-28BC, ionomer (D520), the active area of the prepared MEA is 5cm 2 (2) The test conditions are: the anode gas is hydrogen, the cathode gas is air, the gas flow rate is 500ccm, the gas and battery temperature is 80°C, and the cathode and cathode are 100% RH. As shown in the figure, under the back pressure of 2 bar and 1 bar, the embodiment 1 with enhanced applied voltage performance exhibits 0.29Wcm -2 and 0.23Wcm -2 The high power density shows the feasibility of practical application.
[0087] Figure 3 b is the polarization curve and power density diagram of the proton exchange membrane fuel cell test in Example 1. The fuel cell preparation and test process: (1) CCM method preparation of MEA: the cathode and anode loadings are 4 mg / cm 2 , 0.2mg Pt / cm 2 (40% Pt / C JM); DuPont NC700 proton exchange membrane, diffusion layer SGL-28BC, ionomer (D520), the active area of the prepared MEA is 5cm 2 (2) The test conditions are: the anode gas is hydrogen, the cathode gas is oxygen, the gas flow rate is 500ccm, the gas and battery temperature is 80°C, and the cathode and cathode RH are 100% RH. As shown in the figure, under the back pressure of 2 bar and 1 bar, the embodiment 1 with enhanced applied voltage performance exhibits 0.75Wcm -2 and 0.59Wcm -2 The high power density further demonstrates the feasibility of practical applications.
[0088] Figure 4 A is the SEM image of Example 2. Figure 4 Figure b is the SEM spectrum of comparative example 2. By comparing the two SEM images, the tubular structure of PANI is clearly observed, and the tubular structure does not change significantly after the applied voltage performance enhancement. This shows that after the applied voltage performance enhancement treatment, the sample still maintains the original carbon material morphology.
[0089] Figure 4 Figure c is the XRD spectra of Example 2 and Comparative Example 2. In the XRD spectra, the graphite (002) and (100) crystal planes did not shift, indicating that after the applied voltage performance enhancement treatment, the sample still maintained the original carbon material structure.
[0090] Figure 5 Figure a is a comparison of the oxygen reduction polarization curves of the rotating ring disk electrode in alkaline medium of Example 2 and Comparative Example 2. The electrolyte solution is 0.1M KOH, and the scan rate is 10mV / s. From the linear sweep voltammetry curve (LSV) after iR compensation and N2 background current subtraction, it can be seen that the half-wave potential of Example 2 treated with external voltage performance enhancement is 0.890V, which is 20mV higher than that of the untreated Comparative Example 2. It shows that the external voltage performance enhancement treatment has a significant effect.
[0091] Figure 5Figure b is a comparison of the oxygen reduction polarization curves of the rotating ring disk electrode in the acid medium of Example 2 and Comparative Example 2. The electrolyte solution is 0.1M HClO4, and the scan rate is 10mV / s. From the linear sweep voltammetry (LSV) curve after iR compensation and N2 background current subtraction, it can be seen that the half-wave potential of Example 2 treated with external voltage performance enhancement is 0.750V, which is 5mV higher than that of the untreated Comparative Example 2. It shows that the external voltage performance enhancement treatment has a significant effect.
[0092] Figure 6 A is the SEM image of Example 3. Figure 6 b is the SEM spectrum of comparative example 3. By comparing the two SEM images, the dodecahedral structure of ZIF8 is clearly observed, and the dodecahedral structure does not change significantly after the applied voltage performance enhancement treatment. This shows that after the applied voltage performance enhancement treatment, the sample still maintains the original carbon material morphology.
[0093] Figure 6 Figure c is the XRD spectra of Example 3 and Comparative Example 3. In the XRD spectra, the graphite (002) and (100) crystal planes did not shift, indicating that after the applied voltage performance enhancement treatment, the sample still maintained the original carbon material structure.
[0094] Figure 7 Figure a is a comparison of the oxygen reduction polarization curves of the rotating ring disk electrode in alkaline medium of Example 3 and Comparative Example 3. The electrolyte solution is 0.1M KOH, and the scan rate is 10mV / s. From the linear sweep voltammetry (LSV) curve after iR compensation and N2 background current subtraction, it can be seen that the half-wave potential of Example 3 treated with external voltage performance enhancement is 0.905V, which is 10mV higher than that of the untreated Comparative Example 3. It shows that the external voltage performance enhancement treatment has a significant effect.
[0095] Figure 7 Figure b is a comparison of the oxygen reduction polarization curves of the rotating ring disk electrode in the acid medium of Example 3 and Comparative Example 3. The electrolyte solution is 0.1M HClO4, and the scan rate is 10mV / s. From the linear sweep voltammetry (LSV) curve after iR compensation and N2 background current subtraction, it can be seen that the half-wave potential of Example 3 with enhanced applied voltage performance is 0.765V, which is 15mV higher than that of the untreated Comparative Example 3. It shows that the applied voltage performance enhancement treatment has a significant effect.
Claims
1. A method for enhancing the applied voltage performance of a non-precious metal Fe-NC catalyst, characterized in that: The steps include: Step 1: taking a certain amount of Fe-NC catalyst solid powder and placing it in a container with openings at both ends or a flat container, wherein the Fe-NC catalyst solid powder is placed in the container with openings at both ends or the flat container in a continuous and coherent manner; Step 2: connect the two ends of the Fe-NC catalyst solid powder placed continuously in step 1 to a metal conductive carrier to form a processing device; Step 3: Under normal temperature, normal pressure and a certain atmosphere, the metal conductive carrier is connected with a power supply device to form a closed loop circuit; Step 4: Confirm that the conductive carrier is not short-circuited to avoid subsequent short-circuit situations; Step 5: Turn on the power supply device, apply a certain voltage, and keep the constant voltage stable for a period of time; the certain voltage is 5 V to 30 V, and the period of time is 0.5 h to 10 h; Step 6: Take out the treated solid powder, without adding any activator and without generating any three wastes, and fully grind and crush to obtain the Fe-NC catalyst with enhanced performance.
2. The method according to claim 1, characterized in that The Fe-NC catalyst is commercially available or homemade, and the homemade one includes a Fe-NC catalyst obtained by high-temperature pyrolysis, low-temperature pyrolysis, solid-phase synthesis or liquid-phase synthesis, and the Fe element content is 0.01-1.5 at%, and the N element content is 1-15 at%.
3. The method according to claim 1, characterized in that The certain amount is in the mg to g level, and can reach the kg level under the conditions allowed by the device; the distance between the metal conductive carriers at both ends of the Fe-NC catalyst solid powder is adjusted according to needs.
4. The method according to claim 1, characterized in that: The metal conductive carrier is made of silver, copper or aluminum alloy. The method according to claim 1 , wherein the certain atmosphere is one of air, nitrogen or oxygen.
6. The method according to claim 1, characterized in that The power supply device is a constant voltage DC power supply or a constant voltage AC power supply.
7. The method according to claim 1, characterized in that The performance-enhanced Fe-NC catalyst exhibits increased specific surface area and conductivity compared to the catalyst without performance enhancement, and the FeN modified with keto functional groups has x -ketone active site generation.
8. The method according to claim 1, characterized in that In step 1, the Fe-NC catalyst solid powder is placed continuously in the container with both ends open or in the flat container, and is placed axially continuously by filling or not filling the diameter surface in the tubular container, or placed in a continuous linear manner or stacked in a pile in the flat container.
9. Use of the catalyst with enhanced performance obtained by the method according to claim 1 in metal-air batteries and fuel cells.
